Evaluation of oxidative stability of lamb burger with Origanum vulgare extract. (15th October 2017) - Fernandes, R.P.P.; Trindade, M.A.; Tonin, F.G.; Pugine, S.M.P.; Lima, C.G.; Lorenzo, J.M.; de Melo, M.P.
Highlights: Oregano extract was added to lamb burger in comparison to sodium erythorbate. Antioxidant capacities were set by the Folin-Ciocalteu, DPPH and FRAP methods. Frozen lamb burgers with oregano extract presented better oxidative stability. Addition of oregano extract did not compromise sensory acceptance of lamb burgers. FRAP method better estimated the appropriate amount of oregano extract to be added. Abstract: The objective was to evaluate replacement of sodium erythorbate with a natural antioxidant (oregano extract) on physicochemical and sensory stability of lamb burgers, and determine the appropriate amount. Five treatments were prepared, including control (without antioxidant), sodium erythorbate, and three concentrations of oregano extract (13.32, 17.79 and 24.01 mL/kg), based on antioxidant capacity determined using the Folin-Ciocalteu, 2, 2-diphenyl-1-picrylhydrazyl (DPPH ) and ferric reducing antioxidant power (FRAP) methods, respectively. Burgers containing oregano extract, at the concentration determined by FRAP method, had higher oxidative stability, evidenced by an 80% reduction ( P  < 0.001) in thiobarbituric acid reactive substances, effective inhibition of protein oxidation ( P  < 0.01) and less colour loss during frozen storage. Oregano extract did not impair ( P  > 0.05) consumers' sensory acceptance of the lamb burgers. Under the conditions tested, addition of 24 mL/kg of oregano extract could be recommended as a natural antioxidant in lamb burgers.